25 Endometrial cancer: laparoscopy vs robotic surgery. A large single-institution retrospective analysis. (13th November 2020) - Perrone, E; Capasso, I; Gioè, A; Restaino, S; Distefano, E; Dinoi, G; Scambia, G; Fanfani, F
Abstract : Introduction: Minimally invasive surgery (MIS) is the gold standard for endometrial cancer staging. Among MIS approaches, laparoscopy (LPS) and robotic surgery (RS) are the major techniques. The aim of this study is to compare these two approaches in endometrial cancer staging. Methods: In this large single-institution retrospective study we enrolled 1221 consecutive clinical stage I-II-III endometrial cancer patients undergone MIS surgical staging at the Gynecologic Oncology Unit, Fondazione Policlinico Universitario A. Gemelli IRCCS. We compared 766 patients treated by LPS and 455 by RS, on the basis of perioperative and oncological outcomes (disease free survival, DFS and overall survival, OS). A sub-analysis of the high-risk population was performed in the two cohorts. Results: The two cohorts were homogeneous in terms of perioperative and pathological data. We recorded differences in number of relapse/progression (11.7% in LPS vs 7% in RS, p value= 0.008) and in number of deaths (9.8% in LPS vs 4.8% in RS, p value=0.002). Whereas, in the univariable analysis, the age > 65, grading, the LVSI positivity and the risk group were independent predictors of DFS and OS. In the multivariable analysis the association of the age and grading was significant for DFS and OS. In the sub-analysis, the univariable and the multivariable confirmed the influence of the age in DFS and OS, despite of the MIS approach. Conclusions/implications: In our large retrospective analysis, we confirmed that robotic surgery in superimposable to the standard laparoscopic approach for MIS endometrial cancer staging also for the high-risk population.